2001
DOI: 10.1128/jcm.39.10.3672-3677.2001
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometry Compared with Indirect Immunofluorescence for Rapid Detection of Dengue Virus Type 1 after Amplification in Tissue Culture

Abstract: Dengue virus (DV) was detected early in infected mosquito

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 31 publications
0
24
0
1
Order By: Relevance
“…Sera that have been collected from suspected dengue cases in the first 3-5 days of fever (the viraemic phase) can be used for virus isolation. After an incubation period permitting virus replication, viral identification is performed using dengue-specific monoclonal antibodies in immunofluorescence and PCR assays 63,64,72,73 . Serum is often used for virus isolation but plasma, leukocytes, whole blood and tissues obtained at autopsy can also be used 63,74,75 .…”
Section: Virus Isolationmentioning
confidence: 99%
“…Sera that have been collected from suspected dengue cases in the first 3-5 days of fever (the viraemic phase) can be used for virus isolation. After an incubation period permitting virus replication, viral identification is performed using dengue-specific monoclonal antibodies in immunofluorescence and PCR assays 63,64,72,73 . Serum is often used for virus isolation but plasma, leukocytes, whole blood and tissues obtained at autopsy can also be used 63,74,75 .…”
Section: Virus Isolationmentioning
confidence: 99%
“…We decided to harvest cells at 24 hpi for the FACS titration assay, because the first round of infection peaks at this time point and also because 24 hpi is too early to detect cell-to-cell spread of virus. Previous studies have also indicated that there is minimal cell-to-cell spread of DENV in C6/36 cells at 24 hpi (8). Next, we determined if the FACS assay was able to detect quantitative differences in the number of virus particles in samples.…”
Section: Resultsmentioning
confidence: 94%
“…Within the past 10 years, fluorescence-activated cell sorter (FACS)-based methods have been developed to follow infection and determine titers of viruses such as human immunodeficiency virus, herpesvirus, measles virus, influenza virus, Epstein-Barr virus, and rabies virus (1,4,12,13,16). FACS has also been used to detect DENV in clinical samples and to measure the ability of the virus to infect a variety of cells (2,3,7,8,11,17). Here we report on a FACS-based assay for titrating DENVs and for characterizing the ability of antisera to neutralize the virus.…”
mentioning
confidence: 99%
“…Additionally, this approach has been used to diagnose and titer flaviviruses of importance in veterinary and human public health, such as bovine viral diarrhea virus and DENV [18][19][20] . In this study, we showed that the DENV in clinical samples of patients with acute febrile symptoms can be rapidly detected using PBMCs by FACS, as demonstrated by the observed 29.1% DENV positivity that includes two patients with DENV-1 and 42 patients with DENV-2.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the FACS approach diagnosed a lower number of DENV-positive patients compared to the NS1 assay. This could be probably due to the multiple antigenic determinants that are expressed, both intracellularly and on the cell surface, in the NS1 protein, which is involved in enhancing viral RNA replication and also in the release of infectious viral particles 19 . Additionally, the temporal increase in antiviral immunity, including the appearance of neutralizing antibodies, causes reduced DENV viremia and probably decreases the number of infected cells in blood 33 .…”
Section: Discussionmentioning
confidence: 99%